The Role of Electronic Word-of-Mouth, Social Media Engagement, and Brand Image in Shaping Consumer Purchase Decisions: Evidence from Indonesia's Skincare Industry - Joko Suprianto; Rudianto Rudianto; Jones Zenas Rante (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The rapid growth of the skincare industry in Indonesia has intensified competition among brands, making it essential to understand the factors that influence consumer purchase decisions in digital environments. This study aims to examine the effects of Brand Image, Social Media Engagement, and Electronic Word-of-Mouth (e-WOM) on consumers’ Purchase Decisions toward Kojic Plankton skincare products. A quantitative research approach was employed using a survey method. Data were collected from 134 consumers who had purchased and used Kojic Plankton products. The data were analyzed using multiple linear regression analysis with SPSS software. The results indicate that Brand Image, Social Media Engagement, and e-WOM each have a positive and significant effect on Purchase Decision. Among the three variables, e-WOM emerged as the strongest predictor (β = 0.438), followed by Social Media Engagement (β = 0.276) and Brand Image (β = 0.217). Furthermore, the simultaneous test revealed that the three variables collectively explain 70.8% of the variance in Purchase Decision (R² = 0.708). The findings suggest that consumer-generated information plays a more influential role than firm-generated communication in shaping purchasing decisions within the Indonesian skincare market. This study contributes to the literature on digital marketing and consumer behavior by highlighting the increasing importance of online consumer interactions and social influence mechanisms in social commerce environments. The results also provide practical insights for skincare companies seeking to enhance consumer engagement and strengthen purchase decisions through effective digital marketing strategies.